Newly developed stroke in patients admitted to non-neurological intensive care units - Jo, Sungyang (J Neurol, 2020)
BACKGROUND: Little is known about newly developed stroke in patients admitted to the intensive care unit (ICU). OBJECTIVE: This study aimed to investigate characteristics and outcomes of newly developed stroke in patients admitted to the non-neurological intensive care units (ICU-onset stroke, IOS). METHODS: A consecutive series of adult patients who were admitted to the non-neurological ICU were included in this study. We compared neurological profiles, risk factors, and mortality rates between patients with IOS and those without IOS. RESULTS: Of 18,604 patients admitted to the ICU for non-neurological illness, 218 (1.2%) developed stroke (ischemic, n = 182; hemorrhagic, n = 36). The most common neurological presentation was altered mental status (n = 149), followed by hemiparesis (n = 55), and seizures (n = 28). The most common etiology of IOS was cardioembolism (50% [91/182]) for ischemic IOS and coagulopathy (67% [24/36]) for hemorrhagic IOS. In multivariable analysis, the Acute Physiology and Chronic Health Evaluation II (APACHE II) score (adjusted odds ratio [AOR] = 1.04, 95% CI = 1.03−1.06, P < 0.001), prothrombin time (AOR = 0.99, 95% CI = 0.98−0.99, P = 0.013), cardiovascular surgery (AOR = 1.84, 95% CI = 1.34−2.50, P < 0.001), mechanical ventilation (AOR = 6.75, 95% CI = 4.87−9.45, P < 0.001), and extracorporeal membrane oxygenation (AOR = 2.77, 95% CI = 1.62−4.55, P < 0.001) were related to the development of IOS. Stroke was associated with increased 3-month mortality after hospital discharge (AOR, 2.20; 95% CI, 1.58–3.05; P < 0.001), after adjustment for APACHE II and comorbidities. CONCLUSIONS: Patients who developed IOS had characteristics of initial critical illness and managements performed in the ICU as well as neurological presentations. The occurrence of IOS was related to high morbidity and mortality. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00415-020-09955-5) contains supplementary material, which is available to authorized users.